ADAPTING LANGUAGE TEACHING METHODS TO GENERATION Y'S LEARNING STYLES: A STUDY IN THE CONTEXT OF MODERN EDUCATION - Novri Susanti Suparman; Irsandi, Fadhilah (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2022)
This study investigates the learning preferences of Generation Y students in the context of English language courses in the Riau and Kepulauan Riau regions. Employing a mixed-methods approach, it combines quantitative analysis and qualitative interviews to gain comprehensive insights into how these students approach learning and studying. The quantitative analysis revealed a diverse distribution of learning preferences, with kinesthetic learning being the dominant preference, followed by visual, auditory, and reading/writing preferences. Qualitative insights demonstrated students' adaptability and a willingness to employ a range of learning strategies based on context and content. The study also highlighted the divergence in preferences for technology, emphasizing the need for a blended learning approach. Understanding individual learning styles emerged as a key factor for academic success. These findings underline the importance of flexible, inclusive teaching approaches that cater to the diverse learning needs of Generation Y students.